Community facilitators and barriers to a successful implementation of mass drug administration and indoor residual spraying for malaria prevention in Uganda: a qualitative study - Humphrey Wanzira; Susan Naiga; Ronald Mulebeke; Fred Bukenya; Mariam Nabukenya; Osborn Omoding; Dorothy Echodu; Adoke Yeka (Malaria Journal, 2018)
Abstract Background There is growing interest to add mass drug administration (MDA) to the already existing malaria prevention strategies, such as indoor residual spraying (IRS). However, successful MDA and IRS requires high population-wide coverage, emphasizing the importance of community acceptance. This study’s objectives were to identify community-level facilitators and barriers during the implementation of both MDA and IRS in communities with high malaria transmission intensity. Methods This was a qualitative study conducted in two sub-counties in Katakwi district. Kapujan sub-county residents received two rounds of IRS and MDA while Toroma sub-county residents received two rounds of IRS only. Key informant interviews and focus group discussions were conducted with key influential district and sub-county personnel and community members. Data were analysed using thematic analysis. Transcripts and interview notes from the in-depth interviews were analysed using a coding scheme developed from pre-defined topics together with themes emerging from the data. The Nvivo software program was used to aggregate the data by codes and to present study findings. Results Overall, 14 key informants were interviewed: 4 from Katakwi district and 5 each from Kapujan and Toroma sub-counties. Five focus group discussions were conducted: 4 with community members (men and women), 2 in each sub-county and one with medical staff of Toroma health centre IV. Important themes for consideration raised by the respondents include community sensitization, conducting implementation during the low activity dry season, involvement of government and local leadership, use of the competent locally composed team, community knowledge of malaria effects and consequences, combining interventions and evidence of malaria reduction from interventions. Potential barriers such as spreading of misinformation regarding interventions, the strong unpleasant smell from Actellic and inadequate duration of engagement with the community should be taken into consideration. Conclusion This study documents important community engagement strategies that need to be considered when implementing malaria MDA in combination with IRS, for malaria prevention in such settings. This information is useful for malaria programmes, especially during the design and implementation of such community level interventions.